PEMETAAN KELAS KAPABILITAS KESUBURAN TANAH SEBAGAI DASAR IDENTIFIKASI PERMASALAHAN DAN STRATEGI PENGELOLAAN LAHAN SAWAH - Christanti Agustina; Novalia Kusumarini; Mochtar Lutfi Rayes (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Farmers' lack of understanding of agricultural land characteristics leads to inaccuracy in farm management. As a result, this research aimed to classify soil fertility capability and design soil management strategies based on the limiting factor. This study took place in Malang Regency's Turen District. Soil samples were taken from 45 observation locations throughout 15 LMUs (Land Map Unit). The Fertility Capability Classification (FCC) technique was used to evaluate soil fertility classification utilizing soil texture, pH, organic C, CEC, cation base (K, Na, Ca, Mg), and base saturation. Turen District was found to have eight fertility capability classifications, including Chm (3-8 %), Chm (8-15 %), CLhm (0-3 %), CLhm (3-8 %), LChm (3-8 %), Lhm (0-3 %), Lhm (3-8 %), and Lhm (8-15 %). Single symbol C is interpreted as clay texture for both top and subsoil, as well as a single symbol for L as loamy texture. Symbol CL is interpreted as clay texture on topsoil and loamy texture on subsoil. Symbol LC is interpreted as loamy texture on topsoil and clay texture on subsoil. Symbol h in FCC class is interpreted as low pH (acid), and symbol m as low organic C. Soil pH and organic C content are the two most important limiting parameters for soil fertility.